Heart Rate Variability (HRV) as a Marker of Improved Autonomic Function in PMS: A Homeopathy Intervention-Based Single Blind Randomized Control Study - Nayana P. Barde; Pradip B. Barde; Ajay O. Dahad; Tripathi Shatrugan; Anagha Kulkarni; Tapas K. Kundu (NMO Journal)
Introduction: Pre-menstrual syndrome (PMS) is a prevalent condition contributing to a spectrum of physical and psychological symptoms during the menstrual cycle. Heart rate variability (HRV) stands as a potential tool to delve into the autonomic nervous system’s intricacies. This study aims to bridge this knowledge gap by investigating the relationship between HRV and PMS while concurrently evaluating the efficacy of individualised homoeopathic interventions in managing PMS. Materials and Methods: A prospective case–control study was conducted from August 2020 to April 2021, involving 37 young females aged 16–45 years with diagnosed PMS. Participants were selected through purposive sampling, meeting the Diagnostic and Statistical Manual of Mental Disorders-IV criteria and were randomised into the case (homoeopathy intervention) and control (placebo) groups. Individualised homoeopathic medicines were administered to the case group, while the control group received a placebo. Both groups were followed for 6 months. Autonomic function was assessed using HRV, employing NICOMON, and clinical improvement was evaluated through the Menstrual Distress Questionnaire (MDQ). Statistical analysis included paired t-tests and Pearson’s correlation coefficient. Results: Out of the initially screened 37 subjects, 31 completed the study. The homoeopathy group (n = 15) demonstrated a highly significant improvement in MDQ scores compared to the placebo (n = 16) group (P < 0.00001). HRV analysis revealed significant increases in total power, low-frequency, high-frequency, root mean square of successive normal-to-normal interval differences, NN50 and pNN50%, indicating enhanced autonomic modulation and parasympathetic dominance in the homoeopathy group (P < 0.001, P = 0.006, P = 0.006, P = 0.039, P < 0.001 and P = 0.013, respectively). The miasmatic analysis highlighted an 80% prevalence of sycotic miasm in the PMS cases. Conclusion: Individualised homoeopathic interventions resulted in substantial improvements in autonomic function, as evidenced by HRV metrics, and clinical symptoms in PMS patients. The study sheds light on the potential therapeutic impact of homoeopathy in achieving autonomic balance and relieving PMS symptoms. While acknowledging the study’s limitations, including sample size, these findings suggest avenues for further research in this domain.